Length, diameter and cell wall thickness of tracheids in mature lodgepole pine bole wood - Saranpää, Pekka (Silva Fennica, 1985)
Variation in tracheid morphology were examined for the bole wood of lodgepole pine ( Douglas ex Loudon) grown in Southern and Central Finland. Tracheid lengths were examined in a fast-grown and in slow-grown trees from three stands. Tracheid length increased with increasing height to 4â8 metres and decreased after that, and increased also with increasing age from the pith. The variation between stems was high. The shortest tracheids were about 1.11 mm near the piths and the longest about 4.10 mm near the bark.Pinus contorta